Literasi Keuangan, Gaya Hidup, dan Pendapatan Terhadap Perilaku Pengelolaan Keuangan Keluarga di Desa Adat Kesiut, Kabupaten Tabanan Bali - Gusti Ayu Kade Agung Sintya Prama Dewi; Ni Putu Yeni Astiti; Ni Made Indah Mentari (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
Current world developments have brought about many changes in the economy, especially in the financial management behavior of people who still experience difficulties in managing their finances and end up depending on endless debt. Managing finances is an important thing to do, especially for families in order to achieve a prosperous life. This research aims to explain the influence of financial literacy, lifestyle and income on family financial management behavior in the Kesiut Traditional Village. Determining the number of samples in this study was 88 respondents with a sampling method using purposive sampling technique. The analytical tool used is the Multiple Linear Regression Analysis Technique. The results of this research show that financial literacy and income each have a positive and significant effect on family financial management behavior in the Kesiut Traditional Village. Meanwhile, lifestyle has a negative and significant effect on family financial management behavior in the Kesiut Traditional Village. Suggestions for future researchers can develop this research by conducting research at a wider scope such as city, district, or provincial level.